Penerapan Konsep Green Building Pada Gedung Bangunan Perkantoran Konsultan Lingkungan Di Surabaya - Farah Eka Putri Ramadaniati; Munawar Ali (Jurnal Universal Technic, 2024)
Sustainability Development is one of the target to be achieved in order to maintain the sustainability of future generations without reducing the needs of present. One form of sustainable development that is implemented is green building certification to assess the level of efficiency savings that have been made. This study aiming to analyze the application of green building concept in office buildings. Application analysis was carried on on energy, water, and material efficiency aspects using EDGE program issued by IFC (International Finance Coporation) which is ne of the poviders green building certification. The scope used in this study is that this assessment is carried out with the aim of certifiying exsisting building and post construction. Based on the analysis results, it is known that the value of green building implemtation in office building is 16,63% energy savingi, 34,79% water savings dan 92% material savings